Mass spectrometry reveals distinct proteomic profiles in high- and low-quality stallion spermatozoa. Issue 5 (November 2020) - Griffin, Róisín A; Swegen, Aleona; Baker, Mark; Aitken, Robert John; Skerrett-Byrne, David A; Silva Rodriguez, Antonio; Martín-Cano, Francisco E; Nixon, Brett; Peña, Fernando J; Delehedde, Maryse; Sergeant, Nicolas; Gibb, Zamira
Abstract : The horse breeding industry relies upon optimal stallion fertility. Conventional sperm assessments provide limited information regarding ejaculate quality and are not individually predictive of fertilizing potential. The aim of this study was to harness mass spectrometry to compare the proteomic profiles of high- and low-quality stallion spermatozoa, with the ultimate goal of identifying fertility biomarker candidates. Extended stallion semen ( n = 12) was fractionated using Percoll density gradients to isolate low-quality and high-quality sperm populations. Motility and morphological assessments were carried out, and proteomic analyses was conducted using UHPLC-MS/MS. High-quality spermatozoa recorded higher total (95.2 ± 0.52% vs 70.6 ± 4.20%; P ≤ 0.001) and progressive motilities (43.4 ± 3.42% vs 27.3 ± 4.32%; P ≤ 0.05), and a higher proportion of morphologically normal cells (50.2 ± 4.34% vs 38.8 ± 2.72%; P ≤ 0.05). In total, 1069 proteins were quantified by UHPLC-MS/MS, of which 22 proteins were significantly more abundant in the high-quality sperm population ( P ≤ 0.05). A-kinase anchor protein 4 (AKAP4) and Hexokinase 1 (HK1) were considered possible biomarker candidates and their differential expression was confirmed by immunoblot. Protein expression was significantly correlated with total (AKAP4 R 2 = 0.38, P ≤ 0.01; HK1 R 2 = 0.46, P ≤ 0.001) and progressive motilities (AKAP4 R 2 = 0.51, P ≤ 0.001; HK1 R 2 = 0.55, P ≤ 0.01), percentage rapid (AKAP4 R 2 = 0.29, P ≤ 0.05; HK1 R 2 = 0.58, P ≤ 0.001), straight-line velocity (HK1 R 2 = 0.50, P ≤ 0.01) and straightness (HK1 R 2 = 0.40, P ≤ 0.01). Furthermore, AKAP4 was highly susceptible to adduction by 4-hydroxynonenal (4HNE), which resulted in a global reduction in the phosphorylation profiles following capacitation. In conclusion, the proteomic profiles of high- and low-quality stallion spermatozoa differ substantially, and proteins such as AKAP4 and HK1 could serve as biomarkers of ejaculate quality.